Bio-based PLA_PHB plasticized blend films: Processing and structural characterization. Issue 2 (December 2015) - Armentano, Ilaria; Fortunati, Elena; Burgos, Nuria; Dominici, Franco; Luzi, Francesca; Fiori, Stefano; Jiménez, Alfonso; Yoon, Kicheol; Ahn, Jisoo; Kang, Sangmi; Kenny, José M.
Abstract Bio-based films formed by poly(lactic acid) (PLA) and poly(3-hydroxybutyrate) (PHB) plasticized with an oligomer of the lactic acid (OLA) were used as supporting matrices for an antibacterial agent (carvacrol). This paper reports the main features of the processing and physico-chemical characterization of these innovative biodegradable material based films, which were extruded and further submitted to filmature process. The effect of the addition of carvacrol and OLA on their microstructure, chemical, thermal and mechanical properties was assessed. The presence of these additives did not affect the thermal stability of PLA_PHB films, but resulted in a decrease in their crystallinity and in the elastic modulus for the active formulations. The obtained results showed the effective presence of additives in the PLA or the PLA_PHB matrix after processing at high temperatures, making them able to be used in active and bio-based formulations with antioxidant/antimicrobial performance.